Design automatic baby swing - Makeen, Mohd Amin (2009)
Full-size baby swings designed for indoor use from birth to 25 or 30 pounds typically consist of a seat suspended by a pair of arms attached to a frame with wide-standing, tubular-metal legs. Most swings move from front to back, though several models swing from side to side, cradle-style. Portable travel swings are popular with on-the-go parents. These swings sit low to the ground and are designed to be moved from room to room or stowed in the car for a trip to Grandma’s. Most swings on the market today are battery-operated and driven by a motor. The automatic baby swing was designed using CAD software. The automatic baby swing was designed using CAD software. Then, the design was analyzed using method FEA (ALGOR) software. These analyses were done to find the best design that can optimize the operation for the stress analysis. There is three design have been sketch. The analysis showed that the difference between them. For the third design designs, the result showed that when force apply, the displacement of improvement design that occur is lowest than current design. In conclusion, this improvement can reduce the cost of repairing because the mechanism improvement made can hopefully reduce the failure occur for that specific automatic baby swing.